EKSISTENSI TANAH MASYARAKAT HUKUM ADAT DI KABUPATEN PELALAWAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 TENTANG HUTAN ADAT - Maharani Maharani; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existence of customary law communities is recognized in Article 18B and Article 28I paragraph (3) of the 1945 Constitution. However, there are still actions that can reduce this right, namely the Forestry Law which categorizes Customary Forest under State Forest. This has resulted in a conflict between the two forests. On this matter, the Constitutional Court issued Constitutional Court Decision Number 35 / PUU-X / 2012 recognizing the rights of indigenous peoples to their customary forests. This recognition is provided as long as in reality the customary law community concerned still exists and its existence is recognized. The objectives of this thesis are: First, the existence (existence) of the customary land of the Muara Sakal customary law community (Muaro Sako) in Pelalawan Regency after the Constitutional Court Decision No. 35 / PUU-X / 2012; Second, the inhibiting factor for the existence of the ulayat lands of the customary law community of Muara Sakal (Muaro Sako) in Pelalawan Regency the legal efforts made to maintain the existence of these ulayat lands.This type of research can be classified as a sociological juridical research type, because in this study the author directly conducted research at the location or place being studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Customary Law Community of Muara Sakal (Muaro Sako), in Langgam Village, Langgam District, Pelalawan Regency. The data sources used were primary data, secondary data, tertiary data with interview data collection techniques and literature study.Conclusions can be drawn, first, the existence / existence of the customary law community community rights in Muara Sakal, Langgam sub-district, Pelalawan district, this is indicated by the existence of the customary law community Muara Sakal as the subject of customary rights, there is still Muara Sakal customary land as the object of customary rights, and still there is a relationship between the subject and the object of customary rights. Second, the absence of a Regional Regulation or Regent Decree that provides legal certainty and regulates the protection of customary rights in Pelalawan Regency, especially the ulayat rights / ulayat land of the Muara Sakal customary community (Muaro Sako), as well as the Muara Sakal customary law community have made a number of legal efforts. to obtain legal certainty in the protection and recognition of their customary rights, but it has yet to produce results.Keywords: Existence - customary rights - Muara Sakal customary community